A monomeric von Willebrand factor fragment, Leu-504--Lys-728, inhibits von Willebrand factor interaction with glycoprotein Ib-IX [corrected] - Gralnick, H R (1992)
von Willebrand factor interaction with glycoprotein Ib alpha (GPIb alpha) plays a critical role in the initial phase of platelet adhesion at high shear rates, and it may also play a role in platelet thrombus formation in partially occluded arteries. Previous studies have indicated that two peptides, Cys-474--Pro-488 (peptide 153) and Ser-692--Pro-708 (peptide 154), inhibit von Willebrand factor--GPIb alpha interaction. We have expressed a recombinant fragment of von Willebrand factor, Leu-504--Lys-728 [corrected], with a single intrachain disulfide bond linking residues Cys-509--Cys-695 and examined its ability to inhibit von Willebrand factor--GPIb alpha interactions and platelet adhesion at high shear forces. This recombinant fragment, named VCL, inhibits ristocetin-induced, botrocetin-induced, and asialo-von Willebrand factor-induced platelet aggregation and binding to platelets at an IC50 = 0.011-0.260 microM, significantly lower than the IC50 of peptide 153 or 154, IC50 = 86-700 microM. Peptides 153 and 154 did not result in any inhibition of platelet adhesion (IC50 greater than 500 microM). In contrast, VCL inhibited 50% of platelet adhesion at 0.94 microM and at 7.6 microM inhibited greater than 80% of platelet adhesion to human umbilical artery subendothelium at high shear forces. VCL inhibited the contact and spreading of platelets and also caused a marked decrease in thrombus formation. These studies indicate that VCL may be an effective antithrombotic agent in preventing arterial thrombus formation in areas of high shear force.